2008
DOI: 10.1111/j.1745-4603.2008.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard Scales for Crispness, Crackliness and Crunchiness in Dry and Wet Foods: Relationship With Acoustical Determinations

Abstract: A trained panel developed rating scales for crispness, crunchiness and crackliness for dry and wet foods based on the auditory perception of selected foods. The newly developed scales were then evaluated by 40 untrained panelists and the sound perception of standard foods was assessed through the analysis of the root mean square (RMS) of the 5-s audio waveforms and multidimensional scaling (MDS PRACTICAL APPLICATIONSCrispness, crunchiness and crackliness are not only important and useful descriptors of food te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 46 publications
1
49
0
2
Order By: Relevance
“…i.e. short snapping and longer cracking sounds and the force to bite and chew as perceived on the first bite Duizer and Winger, (2006) One sound event perceived as a sharp, clean, fast, high pitched sound Chauvin et al (2008) Crunchiness Firm and brittle, snaps easily with a typical sound. Sound has a lower pitch, is less loud and longer lasting than for crisp VIickers (1984) Complex failure mechanism that involves repetitive deformation and fracturing of a cell structure.…”
Section: Crispnessmentioning
confidence: 99%
“…i.e. short snapping and longer cracking sounds and the force to bite and chew as perceived on the first bite Duizer and Winger, (2006) One sound event perceived as a sharp, clean, fast, high pitched sound Chauvin et al (2008) Crunchiness Firm and brittle, snaps easily with a typical sound. Sound has a lower pitch, is less loud and longer lasting than for crisp VIickers (1984) Complex failure mechanism that involves repetitive deformation and fracturing of a cell structure.…”
Section: Crispnessmentioning
confidence: 99%
“…Specifically the almond, when compared as a raw product to almonds with different toasting levels, it was observed that when toast level was higher the number of sounds peaks during chewing increased as well [5]. This result might be due to the fact that on those much more toasted almonds there was less free water, thus less water activity [10].…”
Section: Sensory Quality Of the Fruitmentioning
confidence: 99%
“…In fact, the combination of acoustic recording with mechanical tests resulted in a more reliable and objective way of analyzing the sound emissions and allowed the study of different parameters by correlating them with sensory traits [9,10]. The integration of the energy dissipation with the analysis of sound emission has been shown to be crucial for understanding almond crispness and crunchiness.…”
Section: Introductionmentioning
confidence: 99%
“…Sound measurement techniques, which are mainly destructive techniques, have been increasingly applied to gain an understanding of the texture and apple fruits quality (De Belie, De Smedt, & De Baerdemaeker, 2000;De Belie & Harker, 2002;Harker, Maindonald, et al, 2002;Zdunek, Frankevych, Konstankiewicz, & Ranachowski, 2008;Zdunek & Bednarczyk, 2006;Zdunek & Konstankiewicz, 2004;Chauvin, Younce, Ross, & Swanson, 2008;Zarifneshat et al, 2010). Destructive testing consists of recording the sounds produced by instrumental compression probes or by the application of biting or chewing forces in the mouth.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, De Belie et al (2000) and De Belie and performed a mechanical test, also recording and analyzing the sounds produced by panelists during chewing. Chauvin et al (2008) reported that the reproducibility of the trained panel is related to the setting up of common frames of reference auditory textural scales among panelists.…”
Section: Introductionmentioning
confidence: 99%